Nano silicon dioxide oil-water separation membrane and preparation method thereof

By using nano-silica oil-water separation membrane in the oil-water separation membrane and combined with laser etching treatment, the existing membrane separation efficiency is solved, and the existing membrane separation efficiency is achieved, achieving efficient and stable oil-water separation effect.

CN119499890APending Publication Date: 2025-02-25CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411249488.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing oil-water separation membranes have shortcomings in terms of separation efficiency, pollution resistance and stability performance, resulting in low separation efficiency, poor pollution resistance and poor stability performance.

Method used

A nano-silica oil-water separation membrane was used, and the silica nanoparticles were diluted by adding Glue gel solution to the anhydrous ethanol solution, and the vapor phase silica nanoparticles were dispersed evenly in deionized water. Combined with laser etching treatment, the silica nanoparticles were deposited on the substrate surface to form a nanocoated structure.

Benefits of technology

It achieves efficient oil-water separation, with high separation efficiency, low oil-fouling adhesion, strong stability performance, simple and low production, and strong reusability of the membrane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119499890A_ABST
    Figure CN119499890A_ABST
Patent Text Reader

Abstract

The invention discloses a nano silicon dioxide oil-water separation membrane and a preparation method thereof.The preparation method comprises the following steps that S1, a Glue gel solution is added into an absolute ethyl alcohol solution, the Glue gel solution is diluted through electromagnetic stirring, and a diluted gel solution is obtained; s2, fumed silica nanoparticles are added into deionized water, mechanical stirring is performed, ultrasonic dispersion is performed to enable the fumed silica nanoparticles to be uniformly dispersed, and a silica suspension is obtained; s3, the cleaned stainless steel mesh is subjected to laser etching treatment, and a needed base body is obtained; and S4, soaking a substrate in the prepared gel solution, taking out, drying, soaking in the prepared silicon dioxide suspension, taking out, drying, annealing, and depositing silicon dioxide on the surface of the substrate to obtain the nano silicon dioxide oil-water separation membrane. The prepared nano silicon dioxide oil-water separation membrane has the advantages of high separation efficiency, high underwater oil contact angle, high stability, wide applicability and the like, can be widely applied to oil-water separation treatment, and improves the treatment efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention relates to the technical field of oil-water separation membranes, and in particular to a nano silicon dioxide oil-water separation membrane and a preparation method thereof. Background technology:

[0002] With the continuous development of the economy, various industries are constantly developing and the demand for energy is constantly expanding. Human beings' demand for the exploitation and use of oil resources is gradually increasing. In this process, a large amount of oily wastewater is inevitably generated. For example, the occurrence of oil leakage accidents during marine transportation, the discharge of various industrial oily wastewaters, and the disposal of domestic oily wastewater such as catering will form a large amount of oil-water mixtures. These oil-water mixtures pose a serious threat to human health and the ecological environment, and how to separate these oil-water mixtures has become a difficult problem that needs to be solved urgently. Traditional methods for treating oil-water mixtures invest a lot of manpower and material resources to achieve the separation of oil-water mixtures, but with little success. They often face low separation rates, high costs, long processes, and possible secondary pollution problems.

[0003] Researchers have found that many organisms in nature show special wettability due to their own surface structure and special chemical composition. Inspired by this, oil-water mixture membrane separation technology has begun to develop widely. Membrane separation methods are widely used in the field of oil-water mixture separation due to their advantages of low production cost, high separation efficiency and no secondary pollution. It is mainly divided into oil removal type and water removal type. Oil removal type materials are prone to oil contamination due to the oil passing through the separation membrane pores, resulting in poor circulation performance. In contrast, water removal type materials filter aqueous solutions by repelling oil. The materials are not easy to be polluted, have a long service life, and can be separated from oil and water by gravity-driven methods, and the separation process is simple. Superhydrophilic / underwater superoleophobic membrane materials can more effectively reduce the adhesion and contamination of oil droplets on the membrane surface with their unique water film structure. However, due to the limited bonding force between the coating and the substrate, the coating is easy to fall off in actual use, resulting in the loss of wettability. Therefore, the currently prepared membranes have problems such as low separation efficiency, poor anti-pollution ability, and poor stability. Therefore, the development of oil-water separation membranes with good separation efficiency and good stability is still an urgent problem to be solved. Summary of the invention:

[0004] In view of the above problems, the present invention designs a nano-silicon dioxide oil-water separation membrane and its preparation method and application, which can quickly achieve efficient separation of oil-water mixtures, has good stability and high anti-oil pollution performance.

[0005] The technical solution of the present invention is:

[0006] In one aspect, a method for preparing a nano-silicon dioxide oil-water separation membrane is provided, comprising the following steps:

[0007] S1: Adding the Glue gel solution to the anhydrous ethanol solution, diluting it by electromagnetic stirring, and obtaining a diluted gel solution;

[0008] S2: adding fumed silica nanoparticles into deionized water, and performing ultrasonic dispersion after mechanical stirring to make them uniformly dispersed to obtain a silica suspension;

[0009] S3: The cleaned stainless steel mesh is treated with laser etching to obtain the desired matrix;

[0010] S4: soaking the substrate in the prepared gel solution, taking it out and drying it, then soaking it in the prepared silica suspension, taking it out and drying it, and then annealing it to deposit the silica on the surface of the substrate, thus obtaining a nano-silica oil-water separation membrane.

[0011] Preferably, in step S1, the mass ratio of Glue gel to anhydrous ethanol is 1:99.

[0012] Preferably, in step S2, the mass ratio of fumed silica nanoparticles to deionized water is 4:96, and the particle size of the nano-silicon dioxide is 10-20 nm.

[0013] Preferably, in step S3, the base film is 1200 mesh and is ultrasonically cleaned.

[0014] Preferably, in step S3, the laser etching parameters are etching times 1 time, spacing 20 μm, power 16 W and speed 400 mm / s.

[0015] Preferably, in step S1, the electromagnetic stirring is performed at a rotation speed of 1000 rpm for 30 min.

[0016] Preferably, in step S2, stirring is performed at a rotation speed of 500 rpm for 2 hours.

[0017] Preferably, in step S4, the annealing treatment is performed at 550° for 2 hours.

[0018] On the other hand, a nano-silicon dioxide oil-water separation membrane prepared by any of the above-mentioned methods for preparing the nano-silicon dioxide oil-water separation membrane and its application in oil-water separation treatment are also provided.

[0019] The beneficial effects of this application are:

[0020] 1. The nano-silica oil-water separation membrane prepared by the present invention has the characteristics of high separation efficiency, low oil adhesion, strong stability, simple and low-cost preparation, etc., and has good commercial prospects in the field of membrane technology.

[0021] 2. The nano-silica oil-water separation membrane prepared by the present invention improves the roughness microstructure of the substrate surface through laser etching treatment, improves the bonding strength between the silica nanoparticles and the substrate, and achieves high stability. At the same time, the laser etching treatment improves the deposition performance of silica, thereby increasing the contact area between the silica nanoparticles and water, improving the superhydrophilic and superoleophobic properties of the membrane surface, achieving efficient oil-water separation effect and high-throughput performance, and the membrane has strong reusability. Description of the drawings:

[0022] Figure 1 This is a process diagram for preparing a nano-silicon dioxide oil-water separation membrane in Example 1;

[0023] Figure 2 This is an enlarged scanning electron microscope image of the front side of the nano-silicon dioxide oil-water separation membrane of Example 1;

[0024] Figure 3 It is a schematic diagram of the contact angle of the surface of the nano-silica oil-water separation membrane with water in air, the contact angle with oil underwater, and the rolling angle results of Example 1;

[0025] Figure 4 This is the oil-water separation test diagram of the nano-silicon dioxide oil-water separation membrane of Application Example 1;

[0026] Figure 5 This is a test chart of the separation efficiency of the nano-silica oil-water separation membrane for five different oils in Application Example 1;

[0027] Figure 6 This is the test diagram of the friction experiment of nano-silicon dioxide oil-water separation membrane in Application Example 1;

[0028] Figure 7 This is a test diagram of the underwater oil contact angle of the nano-silica oil-water separation membrane at different pH values ​​in Application Example 1; Specific implementation method:

[0029] The embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. The following embodiments are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operation processes are given, but the protection scope of the present invention is not limited to the following embodiments.

[0030] Example 1

[0031] This embodiment prepares a nano-silica oil-water separation membrane. First, a hydrophilic silica nano-coating is prepared by a vapor-phase silica nano-particle deposition method; then, the cleaned stainless steel mesh surface is etched by laser etching technology to obtain an improved substrate; silica nano-particles are deposited on the etched substrate surface by preparing a Glue gel solution and annealing treatment to obtain a nano-coating structure and then modify the substrate to obtain a nano-silica oil-water separation membrane with high separation performance and stable performance. The specific preparation steps are as follows: Figure 1 :

[0032] (a) The stainless steel mesh substrate was cleaned with an ultrasonic cleaner, and then sequentially cleaned in anhydrous ethanol and deionized water for 10 minutes to remove impurities on the substrate surface. After drying, the substrate was etched with a nano-laser, and the etching parameters were 1 etching, 20 μm spacing, 16 W power, and 400 mm / s speed to obtain an etched substrate.

[0033] (b) 1 g of Glue gel was added to 99 g of anhydrous ethanol, and the mixture was electromagnetically stirred at 1000 rpm for 30 min to obtain a diluted gel solution; 4 g of fumed silica nanoparticles were mixed into 96 g of deionized water, and the mixture was mechanically stirred at 500 rpm for 2 h, and ultrasonically dispersed for 30 min to obtain a silica deposition suspension.

[0034] (c) The etched substrate obtained in (a) was immersed in the gel solution (b) for 15 minutes, and then taken out and dried at 80°. Then, it was immersed in the silica deposition suspension (b) for 15 minutes, rinsed with deionized water, and then taken out and dried at 80°. Finally, it was annealed at 550°C for 2 hours to remove the hydrophobic components in the gel solution and fix the silica nanoparticles on the surface of the etched substrate to obtain a nano-silica separation membrane.

[0035] The morphology of the nano-silica oil-water separation membrane of Example 1 was observed using a scanning electron microscope (SEM). Figure 2 As shown in the figure, the surface of the prepared nano-silica oil-water separation membrane is relatively rough and uneven. After laser etching, there are many irregular protrusions and etching pits of different sizes on the surface. At the same time, it is observed that silica nanoparticles are deposited inside and outside the structure, forming an obvious micro-nano dual structure.

[0036] The wettability of the separation membrane was characterized using a SCIB-2000 contact angle goniometer. Figure 3It shows that in the water contact angle test in the air environment, the water contact angle is 0°, and the water droplet can reach the superhydrophilic state within 0.13s after contacting the separation membrane surface; in the underwater oil contact angle test, the underwater oil contact angle is 165°, and the rolling angle is 1.8°. The oil droplet easily leaves the sample surface after contacting the sample surface underwater. Even if a certain pressure is applied, causing the oil droplet to be completely compressed and deformed on the sample surface, the oil droplet can easily leave the surface. This shows that the nano-silica separation membrane sample prepared in Example 1 exhibits extremely strong superhydrophilic / underwater superoleophobic properties, and the coating has extremely low adhesion to oil droplets, showing good anti-oil pollution performance.

[0037] Application Example 1

[0038] The nano-silicon dioxide oil-water separation membrane prepared in Example 1 is Figure 4 As shown in the figure, it is used in the simple oil-water separation device constructed to directly separate various oil-water mixtures by gravity. The experimental device consists of a quartz glass tube, a custom fixture and an operating table. Figure 4 As shown in the figure, the red oil and blue water mixture are automatically separated under the action of gravity. The aqueous solution quickly penetrates and passes through the coating to separate into the beaker, while the oil solution cannot penetrate and is blocked above the separation membrane and remains blocked for 5 minutes, thus achieving the oil-water separation effect. Figure 5 The experiment shown in the figure tests the separation performance of five kinds of oil-water mixtures, including petroleum ether-water mixture, n-hexane-water mixture, edible oil-water mixture, engine oil-water mixture, and gas oil-water mixture, wherein the volume of oil and water in the oil-water mixture is 10 ml respectively. By recycling the aqueous solution and the oil solution, it is calculated that the oil-water separation efficiency of the five mixtures is 99%, indicating that the prepared nano-silica oil-water separation membrane has good applicability and high-efficiency separation performance.

[0039] The nano-silicon dioxide oil-water separation membrane prepared in Example 1 is Figure 6 As shown, it is applied to the friction test device. The separation membrane is fixed under the pressure of a 100g weight and dragged back and forth on a 1000-mesh sandpaper for a total of 40cm per cycle, and the underwater oil contact angle of the sample is measured after the friction test. The underwater oil contact angle of the nano-silica oil-water separation membrane sample remains at 156.3° even after 50 cycles; the separation membrane is immersed in strong acid and alkali solutions with Ph=1, 5, 7, 9, and 12 for 15 days, and the underwater oil contact angle is measured after the corrosion test. After the nano-silica oil-water separation membrane is immersed in solutions with different pH values, the underwater oil contact angle is still higher than 150°. This shows that the prepared nano-silica oil-water separation membrane has good stability.

[0040] The above description of the embodiments is to facilitate the understanding and use of the present invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without having to go through creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the principles of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for preparing a nano-silicon dioxide oil-water separation membrane, characterized in that: The following steps are involved: S1: Adding the Glue gel solution to the anhydrous ethanol solution, diluting it by electromagnetic stirring, and obtaining a diluted gel solution; S2: adding fumed silica nanoparticles into deionized water, and performing ultrasonic dispersion after mechanical stirring to make them uniformly dispersed to obtain a silica suspension; S3: The cleaned stainless steel mesh is treated with laser etching to obtain the desired matrix; S4: soaking the substrate in the prepared gel solution, taking it out and drying it, then soaking it in the prepared silica suspension, taking it out and drying it, and then annealing it to deposit the silica on the surface of the substrate, thus obtaining a nano-silica oil-water separation membrane.

2. The method for preparing a nano-silicon dioxide oil-water separation membrane according to claim 1, characterized in that: In step S1, the mass ratio of the Glue gel to anhydrous ethanol is 1:

99.

3. The method for preparing a nano-silicon dioxide oil-water separation membrane according to claim 1, characterized in that: In step S2, the mass ratio of the fumed silica nanoparticles to deionized water is 4:96, and the particle size of the nano-silicon dioxide is 10-20 nm.

4. The method for preparing a nano-silicon dioxide oil-water separation membrane according to claim 1, characterized in that: In step S3, the base film is 1200 mesh and is ultrasonically cleaned.

5. The method for preparing the nano-silicon dioxide oil-water separation membrane according to claim 1, characterized in that: In step S3, the laser etching parameters are etching times 1 time, spacing 20 μm, power 16 W and speed 400 mm / s.

6. The method for preparing a nano-silicon dioxide oil-water separation membrane according to claim 1, characterized in that: In step S1, during the electromagnetic stirring reaction, the reaction was stirred at a rotation speed of 1000 rpm for 30 minutes.

7. The method for preparing a nano-silicon dioxide oil-water separation membrane according to claim 1, characterized in that: In step S2, the reaction was stirred at 500 rpm for 2 h.

8. The method for preparing a nano-silicon dioxide oil-water separation membrane according to claim 1, characterized in that: In step S4, during the annealing treatment, annealing is performed at 550° for 2 hours.

9. The method for preparing a nano-silicon dioxide oil-water separation membrane according to claim 1, characterized in that: The nano-silicon dioxide oil-water separation membrane is prepared by the preparation method of the nano-silicon dioxide oil-water separation membrane described in claims 1-8.

Citation Information

Patent Citations

  • Preparation method of organic macromolecule polymer coating oil-water separating net

    CN104759118A

  • Super-hydrophobic super-oleophilic porous screen membrane for oil-water separation and preparation method and application thereof

    CN107050928A

  • Superhydrophilic underwater-superlipophobic oil-water separation membrane, and preparation method thereof

    CN107583470A

  • Preparation method for superhydrophilic metal mesh

    CN108815885A

  • Durable super-hydrophilic or super-hydrophobic plastic surface and preparation method thereof

    CN109251345A